2014
DOI: 10.7150/thno.8070
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizer Loaded Nano-Graphene for Multimodality Imaging Guided Tumor Photodynamic Therapy

Abstract: Graphene, a 2-dimensional carbon nanomaterial, has attracted wide attention in biomedical applications, owing to its intrinsic physical and chemical properties. In this work, a photosensitizer molecule, 2-(1-hexyloxyethyl)-2-devinyl pyropheophorbide-alpha (HPPH or Photochlor®), is loaded onto polyethylene glycol (PEG)-functionalized graphene oxide (GO) via supramolecular π-π stacking. The obtained GO-PEG-HPPH complex shows high HPPH loading efficiency. The in vivo distribution and delivery were tracked by fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
139
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(145 citation statements)
references
References 45 publications
(45 reference statements)
3
139
3
Order By: Relevance
“…26 A noncovalent method was used to immobilize photosensitizers onto graphene via π-π stacking, which caused a significant reduction in the fluorescence and ROS generation as a result of a π-π stacking interaction with graphene. 21,22,26,27 To overcome the aforementioned obstacles, we developed a novel ovarian cancer-targeted nanomedicine platform that preserves fluorescence imaging and ROS-generating capabilities of the photosensitizer immobilized on the graphene surface. In our design, graphene nanosheets were chemically conjugated with polypropylenimine generation 4 (PPIG4) dendrimer loaded with silicon Pc derivative to produce a LOGr-Pc-PPIG4 complex ( Figure 1).…”
mentioning
confidence: 99%
“…26 A noncovalent method was used to immobilize photosensitizers onto graphene via π-π stacking, which caused a significant reduction in the fluorescence and ROS generation as a result of a π-π stacking interaction with graphene. 21,22,26,27 To overcome the aforementioned obstacles, we developed a novel ovarian cancer-targeted nanomedicine platform that preserves fluorescence imaging and ROS-generating capabilities of the photosensitizer immobilized on the graphene surface. In our design, graphene nanosheets were chemically conjugated with polypropylenimine generation 4 (PPIG4) dendrimer loaded with silicon Pc derivative to produce a LOGr-Pc-PPIG4 complex ( Figure 1).…”
mentioning
confidence: 99%
“…[61] In this system, GO-PEG nanoplatform increased uptake of the HPPH into the tumor cells, and promoted significantly PDT efficacy on cancer cells with 4 mW/cm 671 nm laser irradiation for 3 min. The GO-PEG-HPPH complex showed high tumor selectivity.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…162 Rong et al demonstrated bimodal°uorescence/PET imaging guided photodynamic therapy of tumors using PEGylated GO sheets loaded with a radiolabeled photosensitizer 64 Cu -HPPH. 163 Similarly, in a separate study, Yan et al demonstrated bimodal°uorescence/PA imaging guided combined photothermal-photodynamic therapy of tumors using PEGylated GO sheets loaded with DVDMS ( Fig. 7(ii)).…”
Section: Multimodal Imaging-guided Phototherapymentioning
confidence: 99%